Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Tax Avoidance, Size Of The Company, Leverage, Age Of The Company On Cost Of Debt In Manufacturing Companies Listed

Abstract: Tax management is the right, appropriate, and effecient application of tax rules in order to achieve income and liquidity accordingly. The tax is twofold: tax avoidance and tax evasion. This research is a purpose to know the effect of tax avoidance towards the cost of debt in manufacturing companies and find about the tax avoidance which includes illegal, but can lead to the injustice that would harm the state. The samples used in this research are 30 manufacture companies listed in Indonesia stock exchange (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Pratama (2017a) stated that the older the company, they tend not to conduct tax avoidance. As the company older, the experience of managing the company and creating a well conservative policy were also increased (Ilaboya & Ohiokha, 2016;Syahwier & Fitriani, 2018), so this company is less probable to commit in a questionable act, while the younger companies were usually managed by less experienced management, so the financial performance would still not be optimal (Kholbadalov, 2012). These arguments showed that younger companies will have a higher probability to do more tax avoidance, so they have a higher probability to participate in tax amnesty.…”
Section: Resultsmentioning
confidence: 99%
“…Pratama (2017a) stated that the older the company, they tend not to conduct tax avoidance. As the company older, the experience of managing the company and creating a well conservative policy were also increased (Ilaboya & Ohiokha, 2016;Syahwier & Fitriani, 2018), so this company is less probable to commit in a questionable act, while the younger companies were usually managed by less experienced management, so the financial performance would still not be optimal (Kholbadalov, 2012). These arguments showed that younger companies will have a higher probability to do more tax avoidance, so they have a higher probability to participate in tax amnesty.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that there is a negative and statistically significant relationship between company age and tax non-compliance and concluded that the longer a business has been in operation, the less prevalence of tax non-compliance found, implying that older companies have been long established in terms of their operations and therefore would be complying to most of the regulations including tax laws. Earlier than this, studies conducted by Evans (1987) in the USA, Yasuda (2005) in Japan, Na et al (2017) in Korea and studies in Indonesia by Syahwier and Fitriani (2017) and Pratama (2017), all investigating the relationship between company age and tax avoidance practices, came to the same conclusion.…”
Section: Presence Of Tax Professionalsmentioning
confidence: 77%
“…The nonfinancial performance disclosure is influenced by the firm's age and size (Wahyuningrum & Djajadikerta, 2020). The firm size and age do not significantly impact earnings management (Indracahya & Faisol, 2017); do not impact the intellectual disclosure of capital (Widiatmoko & Indarti, 2017); and do not affect debt cost (Kinarty, 2020;Syahwier & Fitriani, 2018).…”
Section: Size and Age Of The Companymentioning
confidence: 99%